ANALISIS DAYA DUKUNG PONDASI TERHADAP PENAMBAHAN LANTAI DENGAN STRUKTUR ATAP PLAT BETON GEDUNG RUMAH SAKIT UNIMUS - Agung Sutarto; Abdullah Jalil (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
Semarang City, the capital city of Central Java Province, is one of the cities with a dense population in Indonesia of 1.7 million people and ranks 4th in the region with a population of Central Java. With increasing population growth and limited land for infrastructure development, adding a building floor can solve infrastructure with limited land by utilizing every building space. This study uses the Meyerhof method in 1956 regarding the bearing capacity of deep foundations using NSP-T data and ETABS v18.1 application as an analysis of the superstructure. The results of this study found that the carrying capacity of single and group foundations with Meyerhof calculations with a foundation bearing capacity of 906.189 tons was able to support the maximum load of the superstructure of 647.637 tons after obtaining the addition of one floor and changing the steel roof structure to a concrete slab roof by using the roof as open areas and connections between buildings.